Correction of Anophthalmic Enophthalmos with a Three-Staged Procedure: Two Case Reports. (21st September 2011) - Minagawa, Tomohiro; Shioya, Ryuta; Yamao, Takeshi; Sato, Chigusa; Maeda, Taku
Abstract : Surgical correction of an anophthalmic enophthalmos secondary to inappropriate repair of the eye socket involves several difficult aesthetic issues associated with long-term use of a poorly fitting prosthetic eye. In this paper, we present two cases of anophthalmic enophthalmos. During the treatment of the first patient, unsatisfactory cosmetic problems including lower eyelid retraction, hypoglobus, and severe upper eyelid ptosis were revealed. Accordingly, a three-staged procedure was performed on the second patient, including autologous augmentation of the eye socket, correction of lower eyelid retraction with a cartilage graft, and a frontalis sling procedure to correct upper eyelid ptosis.